(untitled) (Nativa, 2023)
O cultivo de plantas suculentas se popularizou no Brasil, aumentando a necessidade da compreensão do comportamento das espécies sob condições diferentes de produção. Assim, objetiva-se com este trabalho avaliar a influência de fertilizante enraizador, temperatura e luminosidade na emergência de brotações e raízes para espécies suculentas. Três experimentos foram conduzidos de novembro 2020 a fevereiro 2021, em casa de vegetação, com delineamento inteiramente casualizado, com quatro repetições, cada estudo com uma espécie: Echeveria elegans, Graptosedum Francesco Baldi e Sedum adolphii. Para cada espécie, os tratamentos foram arranjados em esquema fatorial (3x2), o fator A comparou fertilizante enraizador comercial e duas testemunhas (água e controle); e o fator B, as estacas foliares das espécies foram submetidas a dois ambientes de temperatura e luminosidade (24,8 oC e 449,8 µmol/m2s; 5 oC e 0 µmol/m2s). Avaliou-se aos 30 dias de instalação dos estudos: índice de velocidade de brotação; porcentagem de brotação; comprimento médio das raízes; comprimento médio do broto e massa seca total. O fertilizante beneficia a emissão de brotações e raízes na Echeveria elegans, porém tais efeitos não são verificados na ausência de luminosidade e baixa temperatura (5 oC). Esse ambiente também prejudicou as demais espécies avaliadas. Palavras-chave: Echeveria elegans; Graptosedum Francesco Baldi; Propagação; Sedum adolphii. Emergency of sprouts and roots of suculent species due to the application of rooting fertilizer, in contrasting environments ABSTRACT: The cultivation of succulent plants became popular in Brazil, increasing the need to understand the behavior of species under different conditions. Thus, the aim of this work is to evaluate the influence of plant rooting fertilizer, temperature, and light intensity on the emergence of new shoots and roots for succulent species. Three experiments were conducted from November 2020 to February 2021, in greenhouse, with completely randomized design, with four replications, each study with one species: Echeveria elegans, Graptosedum Francesco Baldi and Sedum adolphii. The treatments for each species were arranged in factorial scheme (3x2), factor A compared commercial plant fertilizer and two checks (water and control); and factor B, the leaf cuttings of the species were submitted to two environments in relation to temperature and light (24.8 oC and 449.8 µmol/m2s; 5 oC and 0 µmol/m2s). It was evaluated at 30 days of installation: sprouting speed index; sprouting percentage; average root length; average sprout length and total dry mass. The fertilizer benefits the emission of shoots and roots in Echeveria elegans, but such effects are not observed for absence of light and low temperature (5 oC). This environment also harmed the other species evaluated. Keywords: Echeveria elegans; Graptosedum Francesco Baldi; Propagation; Sedum adolphii.